Household income mobility in India, 1993–2011. Issue 4 (25th June 2022) - Azam, Mehtabul
Abstract: Using a nationally representative longitudinal survey and both absolute and relative measures of mobility, we examine the differences in income mobility across social groups in rural India over 1993–2004 and 2004–2011. We find significant differentials in income mobility that mirror the historical Indian caste system hierarchy. Conditional on having similar rankings in base‐period income distribution, the Forward Hindu Caste households have the highest (lowest) probability of upward (downward) income mobility, followed by the Other Backward Caste, Scheduled Caste, and Scheduled Tribe households. Moreover, these differentials in mobility are only partially explained by differences in household characteristics. We find similar but smaller differentials in mobility across social groups in Urban India. We also find that urban population witnessed a higher (lower) upward (downward) mobility during 2004–2011 compared with rural population. Furthermore, we find similar differentials in mobility using consumption as a measure of well‐being.